Nano-TiO₂-treated recycled aggregate-based photocatalytic mortar: Efficient NOx removal and mathematical modeling across diverse operational scenarios - Xue-Fei Chen; Xiu-Cheng Zhang; Xiangping Xian; S Thomas Ng (Developments in the Built Environment)
Nano-TiO2-treated (NT) recycled concrete aggregates (RA) were successfully integrated into the built environment by producing green photocatalytic mortar. Employing various microstructural characterization techniques, it was revealed that the old mortar layer of the RA possessed a porous surface structure, providing a significant specific surface area conducive to effective NT loading. A stable Ti-O-Si chemical bond was established between the surface of the RA and the NT through a hydroxylation treatment process, ensuring the durability of the green photocatalytic mortar during its manufacture and deployment within the built environment. This innovative mortar demonstrated an exceptional NOx removal efficiency of c.a. 90.75%. A predictive model was developed using the Back Propagation Neural Network, integrating experimental and theoretical data to optimize mortar performance across various scenarios. The findings mark a significant advancement in using RA in construction, contributing to sustainable development in the built environment.